Evaluating behavioral skills training to teach safe tackling skills to youth football players. Issue 4 (20th September 2017) - Tai, Sharayah S. M.; Miltenberger, Raymond G.
Abstract : With concussion rates on the rise for football players, there is a need for further research to increase skills and decrease injuries. Behavioral skills training is effective in teaching a wide variety of skills but has yet to be studied in the sports setting. We evaluated behavioral skills training to teach safer tackling techniques to six participants from a Pop Warner football team. Safer tackling techniques increased during practice and generalized to games for the two participants who had opportunities to tackle in games.